Genetic Risk of Trigger Finger: Results of a Genomewide Association Study. Issue 2 (August 2020) - Sood, Ravi F.; Westenberg, Ritsaart F.; Winograd, Jonathan M.; Eberlin, Kyle R.; Chen, Neal C.
Abstract : Background: Trigger finger, or stenosing tenosynovitis, is one of the most common conditions affecting the hand, yet its pathophysiology remains poorly understood, and genetic association studies of trigger finger are lacking. The purpose of this study was to identify single-nucleotide polymorphisms associated with trigger finger through a genomewide approach. Methods: The authors performed a case-control genomewide association study in the Partners HealthCare Biobank. Single-nucleotide polymorphism– and gene-based association analyses were carried out after quality control, imputation, and filtering. Results: Among 942 trigger finger cases and 24, 472 controls, the authors tested 7, 846, 471 single-nucleotide polymorphisms for association with trigger finger. In the single-nucleotide polymorphism–based analysis, a single locus on chromosome 13 corresponding to KLHL1 met the genomewide significance threshold (lead single-nucleotide polymorphism rs59988404; OR, 1.74; 95 percent CI, 1.47 to 2.07; p = 1.99 × 10 −10 ). After mapping, gene-based analysis demonstrated a significant association with POLE2 ( p = 7.53 × 10 −7 ) on chromosome 14. Among trigger finger cases, rs59988404 genotype was significantly associated with the total number of trigger finger procedures performed ( p = 0.026). Conclusions: In the first reported genomewide association study of trigger finger, the authors report significant associations of KLHL1 and POLE2 with risk of trigger finger. The authors' results may help to elucidate the pathophysiology of trigger finger and facilitate an individualized, precision-medicine treatment approach. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III. Abstract : Supplemental Digital Content is available in the text.